Indoor Positioning by LED Visible Light Communication and Image Sensors - Mohammad Shaifur Rahman; Md. Mejbaul Haque; Ki-Doo Kim (Institute of Advanced Engineering and Science, 2011)
High power white LEDs are expected to replace the existing lighting technologies in near future which are also suggested for visible light communication (VLC). We proposed an algorithm for high precision indoor positioning using lighting LEDs, VLC and image sensors. In the proposed algorithm, four LEDs transmitted their three-dimensional coordinate information which were received and demodulated by two image sensors near the unknown position. The unknown position was then calculated from the geometrical relations of the LED images created on the image sensors. We described the algorithm in details. Simulation of the proposed algorithm was done and presented in this paper. This technique did not require any angular measurement which was needed in contemporary positioning algorithms using LED and image sensor. Simulation results showed that the proposed system could estimate the unknown position within the accuracy of few centimeters. Positioning accuracy could be increased by using high resolution image sensors or by increasing the separation between the image sensors.DOI:http://dx.doi.org/10.11591/ijece.v1i2.165